Fault Characterization of Radial AC Microgrid Containing Multiple Distributed Energy Resources at Medium and Low Voltage Levels - Hoeft, Nicholas; Vygoder, Mark; Cuzner, Robert (International Conference on Renewable Energy Research and Applications (Online), 2019)
In terms of protection, radially distributed AC systems are the most common and have the advantage of simplicity. However, with the addition of distributed energy resources and multiple operating modes, simplicity diminishes, and conventional AC system protection approaches may no longer be adequate. In the case of microgrids, grounding methods and cable lengths must also be considered. If a fault scenario occurs, current can feed from multiple sources and has high potential to affect many branches, with the possible result of isolating the wrong part of the system or isolating a large part of the full system. Both of these results will result in poor system availability. Full characterization of each fault scenario is required to determine the protection scheme, taking into account each system configuration. This paper provides a characterization of line-to-line, line-to-ground, and three-line-to-ground faults at any possible location in a commercial microgrid. This characterization gives insight into protection considerations, e.g. using conventional methods of mechanical circuit breakers or if additional protective relaying capabilities are needed.